Representaciones Sociales Sobre Conductas Ecologicas En El Personal Administrativo De Una Institución Hospitalaria De Bogotá (2016)
This paper describes the social representations of ecological behavior, the administrative staff of a hospital in Bogota; to comply with this objective descriptive qualitative research design, and technical information collection and then open interview content analysis was used was raised. 6 active population are employees of a hospital for at least 6 months to be worked onit.